INTERVENSI DALAM PEMBANGUNAN DAERAH DI INDONESIA - Nesthy Kheren Nadia; Sazili Sazili (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Indonesia's development program has actually been ongoing and relentless. However, development is not felt significantly by the people of Indonesia. due to centralized development. The cessation of the era of centralized development cannot be separated from the role of government intervention in desiring a new paradigm of national development that is far better and more equitable. When the law on decentralization or regional autonomy appeared, regional governments were required to be able to take care of the development of their respective regions. However, decentralization or regional autonomy is not always good and many planned developments do not go smoothly. Intervention by law and central government occurred in the implementation of development in the region. The interventions carried out by the legislature and the central government are expected to assist the government in developing the region. Interventions can be carried out according to the capacity, duties and functions of each of these institutions. With interventions, development in areas that previously did not go according to budget and schedule can assist its implementation so that development can be truly optimal. But the intervention given must be in accordance with the portion and not too excessive.